An examination of land market values and influencing factors the case of residential lots in Cinco Hermanos Subdivision, Barangay Industrial Valley Complex (IVC), District 1, Marikina City - Ras, Jules Lemuel T. (School of Urban and Regional Planning, University of the Philippines Diliman, 2016)
Land market values of residential lots in subdivisions are expected to vary across lots of different physical characteristics and to steadily increase over time as the surrounding environment and socio-economic conditions change. Zonal and assessed value of land are expected to be periodically adjusted to reflect change in market values. Using the case of residential lots in a subdivisions Marikina City, this study examined (1) the relationship between physical characteristics and lot price at first sale, (2) how disaster risk factors and changes in socio-economic and other factors relate to the pattern of change in lot prices over time, and (3) how adjustments in zonal and assessed values compared to actual changes in lot prices overtime. The study found only the distance of the lot to the subdivision ingress and egress (gate) to be significantly correlated to lot price. The general lack of significant relationship between lot price and the other lot characteristics (i.e., siting, shape, size, frontage, elevation)is attributed to the fact that the land prices data used in the analysis were no longer the suggested or standard price set by the developer but rather were "arms-length transaction" prices. . The study findings also point to the presence in the immediate surroundings of Cinco Hermanos Subdivision of among others, business establishment and services, CBDs, schools, churches, recreations, amenities, institutional agencies, hospitals, and the availability of transportation infrastructures such as roads, bridges, and railways, and even of other residential subdivisions, to be contributory factors to the steady upward movement of land price per square meter. Similar upward movement in unit price was observed even in lots where geo-hazards like earthquake fault and flooding were present. The study also found assessed and zonal values to be about 50% of the prevailing land market values using average actual sale prices of lots in Cinco Hermanos as reference. The study concludes with a discussion of the findings' implications for local development planning and these include among others some recommendations as follows: (1) Direct regulation of the residential use of lands with geo-hazards, (2)Strengthening of disaster risk reduction measures in such areas including information dissemination,(3) Strengthening of cadastral information system, and (4) Policy about land aooraisal and disclosures of geo-hazards.